2007
DOI: 10.1063/1.2711659
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of photovoltages in organic dye-sensitized solar cells by Li intercalation in particulate TiO2 electrodes

Abstract: Photovoltages of nanoporous TiO2 solar cells sensitized by organic dyes are found to be improved by up to 200mV with a negligible decrease in photocurrent by treating TiO2 electrodes with intercalation of Li. The enhancement in photovoltage is explained in terms of the formation of a dipole layer due to adsorption of Li ions on the TiO2 surface generated by the reaction of intercalated Li atoms with moisture in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…4,5 They thus become ideal candidates as dye photosensitizers. [6][7][8][9][10][11] In addition, these dye molecules have other applications in laser dyes, 4, 5 solvation and fluorescence probe molecules. [12][13][14][15][16][17][18][19][20][21][22] Coumarin 343 (C343, see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 They thus become ideal candidates as dye photosensitizers. [6][7][8][9][10][11] In addition, these dye molecules have other applications in laser dyes, 4, 5 solvation and fluorescence probe molecules. [12][13][14][15][16][17][18][19][20][21][22] Coumarin 343 (C343, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1) is one of 7-amino coumarins and has been already used in DSSC. 7,[9][10][11] It has a rigid julolidine structure and was first reported in 1975 with a high quantum yield of fluorescence in ethanol. 4 Its crystal was first prepared from a chloroform solution by slow evaporation in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Adding lithium to the electrolyte allows control of the electron injection yield from the dye to the TiO 2 electrodes [20][21][22][23] and the rate of interfacial charge recombination, 24 as well as increasing both the conductivity of the electrodes, 25 and resultant photovoltages. 26 Although surface polarization is likely to play a large role, 25 given the ease with which Li intercalates into anatase TiO 2 some interstitial Li is expected to be present. It has been suggested that interstitial lithium modifies the distribution of charge traps within the TiO 2 substrate, [26][27][28] with a consequential effect on the dynamics of charge carriers diffusing through the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…26 Although surface polarization is likely to play a large role, 25 given the ease with which Li intercalates into anatase TiO 2 some interstitial Li is expected to be present. It has been suggested that interstitial lithium modifies the distribution of charge traps within the TiO 2 substrate, [26][27][28] with a consequential effect on the dynamics of charge carriers diffusing through the electrode. This interaction between intercalated lithium and electrons resident within the Ti sublattice has theoretical support from interatomic forcefield calculations of Olson et al 27 who predicted strong binding between interstitial Li and a neighboring Ti in a +3 oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltages of nanoporous TiO 2 based DSSCs were improved by up 200 mV with negligible decrease in photocurrent by treating TiO 2 electrodes with an intercalation of Li + . 53 The enhancement of photovoltage is explained in terms of the formation of a dipole layer due to adsorption of Li + on the TiO 2 surface generated by the reaction of intercalated Li atoms with moisture in the air. Addition of lithium salt Li[(CF 3 SO 2 ) 2 N] to the spin coating solution of the hole conductor also resulted in a strong performance increase in the final device.…”
Section: Electrochemical Photovoltaic Cells Without Dyesmentioning
confidence: 99%